Physiotherapy assessment of temporomandibular joint in pregnant women and prevalence of dysfunctional signs and symptoms - Juliana P. Tosato; Daniela A. Biasotto-Gonzalez; Tabajara O. Gonzalez (Universidade Estadual de Campinas, 2015)
In the pregnancy many transformations and adaptations occur. These alterations can be predisposing factors to Temporomandibular Disorders (TMD), once the Temporomandibular Joint (TMJ) is vulnerable to intrinsic and extrinsic factors. The proposal of this study was to evaluate the TMJ of pregnant women, checking the prevalence of signs and symptoms of disorder in this joint. To accomplish the study, 22 pregnant were analyzed and divided in first, second, third trimester and those who have baby in the past three months. The dynamics of the mandible movements was observed and the higher amplitude was found in the third trimester. Was noted in the same group a generalized hipermobility and signs of Temporomandibular Disorders, including muscular pain and joint symptoms. It was also observed cervical posture alterations which could be responsible for the presence of symptoms in the others trimesters. Parafunctional habits were also checked in all groups. Therefore, the adaptations presented in the pregnant women such as joint hipermobility, posture alteration, and other modifications can influence the TMJ biomechanic, provoking TMD in pregnant women and in other people who also present these disturbances.